Action feedback affects the perception of action-related objects beyond actual action success - Kirsch, Wladimir; Königstein, Elisabeth; Kunde, Wilfried (Frontiers in Psychology, 2014)
Successful object-oriented action typically increases the perceived size of aimed target objects. This phenomenon has been assumed to reflect an impact of an actor’s current action ability on visual perception. The actual action ability and the explicit knowledge of action outcome, however, were confounded in previous studies. The present experiments aimed at disentangling these two factors. Participants repeatedly tried to hit a circular target varying in size with a stylus movement under restricted feedback conditions. After each movement they were explicitly informed about the success in hitting the target and were then asked to judge target size. The explicit feedback regarding movement success was manipulated orthogonally to actual movement success. The results of three experiments indicated the participants’ bias to judge relatively small targets as larger and relatively large targets as smaller after explicit feedback of failure than after explicit feedback of success. This pattern was independent of the actual motor performance, suggesting that the actors’ evaluations of motor actions may bias perception of target objects in itself.